2023
DOI: 10.1111/apt.17395
|View full text |Cite
|
Sign up to set email alerts
|

Letter: tricky reactions to switch back from subcutaneous to intravenous vedolizumab in patients with inflammatory bowel disease

Abstract: LINKED CONTENT This article is linked to Volkers et al papers. To view these articles, visit https://doi.org/10.1111/apt.17153 and https://doi.org/10.1111/apt.17407

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Safety concerns have been raised regarding switch back to IV once being established on SC treatment. 22 , 23 In the present study, 4 patients switched back to IV due to ISRs, and 3 of these patients experienced AEs at consecutive infusions, 1 case leading to discontinuation of VDZ. Our observations are consistent with observations made by Volkers et al, where 1 out of 4 patients switching back to IV due to ISRs had to discontinue VDZ.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Safety concerns have been raised regarding switch back to IV once being established on SC treatment. 22 , 23 In the present study, 4 patients switched back to IV due to ISRs, and 3 of these patients experienced AEs at consecutive infusions, 1 case leading to discontinuation of VDZ. Our observations are consistent with observations made by Volkers et al, where 1 out of 4 patients switching back to IV due to ISRs had to discontinue VDZ.…”
Section: Discussionmentioning
confidence: 56%
“… 4 , 5 , 15–18 Yet, recently published reports disclosed that some patients with AEs on SC VDZ, experienced AEs also when switching back to IV treatment. 22 , 23 Thus, further safety data when switching back to IV VDZ are needed.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the letter by Richard et al 1 in relation to our recently published study reporting real-world experience of switching from intravenous (IV) to biweekly subcutaneous (SC) vedolizumab maintenance treatment for patients with inflammatory bowel diseases (IBD). 2 Richard et al reported seven (out of a total of 10) patients who switched back from SC to IV vedolizumab due to injection site reactions and then developed infusion reactions after IV vedolizumab administration.…”
Section: Letter: Tricky Reactions To Switch Back From Subcutaneous To...mentioning
confidence: 99%